Persistent organic pollutants in cork used for production of wine stoppers. - Mazzoleni, V.; Dallagiovanna, L.; Trevisan, M.; Nicelli, M. (Chemosphere, 2005)
Owing to the lipophilic character of some components of cork and the long periods in the open air (during growth and barks storage), there is a risk of the cork becoming environmentally polluted. Moreover, cork stoppers are in contact with wines for periods ranging from a few months to several years; so they must maintain high levels of hygiene. The present work aims to investigate the level of PCBs, organochlorine pesticides, and PAHs in cork from different countries, used for the manufacturing of one-piece wine stoppers. Samples of cork were analysed using a multi-residue method. PCBs were not detected in all the samples; only a few samples contained detectable amounts of DDE; phenanthrene and anthracene were found in all the samples and fluoranthene in fewer cases. It was not possible to find a significant correlation between POPs concentration and origin of cork. Globally, the detected amounts are consistent with values found in foods, so the investigated cork show a suitable hygienic quality.
The following values have no corresponding Zotero field: accession-num: 15694474
Keywords: Cork; Organochlorine pesticides; PAHs; PCBs

Effects of electron beam irradiation on cork volatile compounds by gas chromatography mass spectrometry - Careri, M.; Mazzoleni, V.; Musci, M.; Molteni, R. (CHROMATOGRAPHIA, 1999)
The effects of electron beam irradiation on cork volatile compounds was studied at different doses (25, 100, 1000 kGy), Volatiles we:re isolated from cork using the dynamic headspace-sampling technique, then identified by gas chromatography-mass spectrometry (GC-MS). Similar gas chromatographic profiles were obtained for non-irradiated and irradiated corks. Quantitative differences induced by the three doses were evaluated by calculating peak areas for each compound identified. The quantitative differences between non-irradiated corks and those irradiated at 25 kGy were significant for only a few substances, when:as significant quantitative differences were found in samples irradiated at 100 and 1000 kGy. For these doses, the content of volatile compounds generally increased, especially that of aliphatic hydrocarbons and carbonyl compounds. The behaviour of radiolytic hydrocarbons indicates that the mechanisms proposed for their formation in irradiated foods could take place even in cork.
The following values have no corresponding Zotero field: pub-location: ABRAHAM-LINCOLN-STRABE 46, POSTFACH 15 47, D-65005 WIESBADEN, GERMANY publisher: VIEWEG
Keywords: cork volatiles; dynamic headspace sampling; electron beam irradiation; gas chromatography mass spectrometry; radiolysis-induced compounds